Nutritional anaemia and malaria in pre-school and school aged children (2008)
Background: The most common cause of anemia is a deficiency of iron; but it may also be caused by deficiencies of folates, vitamin B12 and protein. Some anemias are not caused by nutritional factors, but by congenital factors and parasitic diseases such as malaria. This study attempted to estimate the prevalence of anemia among pre-school and school- aged children in two rural areas of Odogbolu Local government area, and to determine whether its cause was nutritional or could be attributed to malaria. Methods: A total of 177 children between the ages of 2 and 11 years were included in the study. Children were examined for malaria parasites by microscopy. The World Health Organization (WHO) age-adjusted cut-off for hemoglobin and hematocrit were used to classify anemia. An enzyme linked immunosorbent assay for serum ferritin was compared with standard methods of determining iron deficiency. Under- nutrition (stunting, wasting and underweight) was classified according to the National Centre for Health Statistics standards. Values below □ - 2SD were defined as mild-moderate under-nutrition, and those below □ -3SD as severe malnutrition. Results: Most of the children were anemic, 87.1%, having PCV values below the 32% cut-off and 95% with hemoglobin levels lower than the 11g/dl, although parasite prevalence and density were low. Malnutrition was patent; 36% of the children were stunted, 18.3% wasted and 44.2% underweight. Serum ferritin was more sensitive than PCV in detecting anemic children. Although anemia was higher in boys and preschoolers compared to girls and school aged children, the difference was significant only in preschoolers (P = .004). Anaemia was also significantly higher in Irawo village school than in Iloti (P = .0001) Conclusion: The anemia detected in this population may be due more to under-nutrition than to malaria.